Enhancing the Release Efficiency of a Molecular Chemotherapeutic Prodrug by Photodynamic Therapy - Yuan, Jie; Zhou, Qian‐Hui; Xu, Shuai; Zuo, Qing‐Ping; Li, Wei; Zhang, Xing‐Xing; Ren, Tian‐Bing; Yuan, Lin; Zhang, Xiao‐Bing (Angewandte Chemie International Edition, 2022)
Tumor‐specific, hypoxia‐activated prodrugs have been developed to alleviate the side effects of chemotherapy drugs. However, the release efficiency of hypoxia‐activated prodrugs is restricted by the degree of tumor hypoxia, which further leads to poor cancer treatment effects. On the other hand, oxygen is consumed gradually in photodynamic therapy (PDT), which aggravates hypoxia at the tumor site. In this study, we combined hypoxia‐activated prodrugs with PDT agents to promote the prodrugs release, thereby improving their bioavailability and therapeutic effects. As a proof of concept, a mitochondria‐targeted molecular prodrug, CS‐P, was designed and synthesized. It can be selectively activated by tumor hypoxia to release chemotherapeutic drugs and photosensitizers, and then further discharge drugs after light irradiation. The design strategy proposed in this paper provides a new idea for enhancing hypoxia‐activated prodrug release and real‐time monitoring prodrug release. A mitochondria‐targeted molecular prodrug, namely CS‐P, was designed and synthesized to demonstrate the feasibility of using the PDT process to effectively promote the release of hypoxia‐activated drugs. The experimental results indicated that CS‐P can be selectively activated by tumor hypoxia to release chemotherapeutic drugs and photosensitizers, and then further release chemotherapeutic drugs after light irradiation. The design strategy proposed provides a new idea for enhancing hypoxia‐activated prodrugs release.